2017
DOI: 10.1038/nchembio.2344
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes reversal by inhibition of the low-molecular-weight tyrosine phosphatase

Abstract: Obesity-associated insulin resistance plays a central role in type 2 diabetes. As such, tyrosine phosphatases that dephosphorylate the insulin receptor (IR) are potential therapeutic targets. The low molecular weight protein tyrosine phosphatase (LMPTP) is a proposed IR phosphatase, yet its role in insulin signaling in vivo has not been defined. Here we show that global and liver-specific LMPTP deletion protects mice from high-fat diet-induced diabetes without affecting body weight. To examine the role of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
62
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 53 publications
6
62
1
Order By: Relevance
“…Consistent with the above-mentioned role of LMPTP in dephosphorylating the IR, we found that global and liver-specific LMPTP KO protects mice from high-fat diet induced diabetes without affecting body weight[30]. To validate LMPTP as a new type 2 diabetes target, we developed an LMPTP inhibitor[30]. This series was identified by compound screening using a high concentration of OMFP substrate, such that the enzyme was at V max .…”
Section: Trends In Small-molecule Ptp Inhibitor Developmentmentioning
confidence: 71%
See 3 more Smart Citations
“…Consistent with the above-mentioned role of LMPTP in dephosphorylating the IR, we found that global and liver-specific LMPTP KO protects mice from high-fat diet induced diabetes without affecting body weight[30]. To validate LMPTP as a new type 2 diabetes target, we developed an LMPTP inhibitor[30]. This series was identified by compound screening using a high concentration of OMFP substrate, such that the enzyme was at V max .…”
Section: Trends In Small-molecule Ptp Inhibitor Developmentmentioning
confidence: 71%
“…Uncompetitive inhibition occurs when an inhibitor binds to an enzyme-substrate complex[8]. Consistent with the above-mentioned role of LMPTP in dephosphorylating the IR, we found that global and liver-specific LMPTP KO protects mice from high-fat diet induced diabetes without affecting body weight[30]. To validate LMPTP as a new type 2 diabetes target, we developed an LMPTP inhibitor[30].…”
Section: Trends In Small-molecule Ptp Inhibitor Developmentmentioning
confidence: 74%
See 2 more Smart Citations
“…Research over the past decades has established that aberrant PTP signaling, through genetic mutation or altered expression levels, is associated with many human diseases and PTP knock-out mice studies have identified potential therapeutic opportunities for PTP inhibitors (reviewed in [ 11 , 12 , 13 , 14 , 15 ]). The challenges associated with small molecule PTP drug development have been well documented and as yet there are no clinically approved drugs targeting PTPs, although recent notable developments have included the identification of the compound SHP099 [ 16 ], a src homology 2-containing protein-tyrosine-phosphatase (SHP2) inhibitor for treatment of cancers, and low-molecular-weight PTP (LMPTP) inhibitors for diabetes [ 17 ]. Here we provide an update on the emerging area of receptor PTP-targeted biotherapeutics for CD148, VE-PTP, RPTPσ, CD45, RPTPÎł, and RPTPζ, and discussion of future potential in this area.…”
Section: Introductionmentioning
confidence: 99%